The Direct and Indirect Costs of Tax Treaty Policy : Evidence from Ukraine - Balabushko, Oleksii; Beer, Sebastian; Loeprick, Jan; Vallada, Felipe (World Bank, Washington, DC, 2017)
This study combines macro and micro data to quantify the revenue effects of double tax treaties. First, drawing on administrative information, the study estimates the tax sensitivity of income flows (dividend, interest, and royalty payments) at an aggregate level. The analysis finds important direct revenue costs linked to treaty restrictions on taxing rights, especially for flows into a few major investment hubs. However, high elasticities of income flows also suggest that increases in withholding rates at the individual treaty partner level would not necessarily result in more revenue collection. Second, the study uses firm-level information to estimate the sensitivity of reported profitability to changes in the relevant treaty network. The analysis of the reported earnings of multinational enterprise affiliates in Ukraine suggests that the ownership structure and operations with affiliates in certain jurisdictions explain reported profitability, and should thus receive increased attention in risk assessment and transfer pricing audit activities.